Pengaruh Project Based Learning Berbasis Lingkungan Terhadap Literasi Lingkungan Peserta Didik - Kurnia Putra, Alfyananda; Dian Kristanti, Queentasya Vanti; Oktavia, Imanda (Universitas Muhammadiyah Surabaya, 2024)
Overcoming the waste problem can be done with various methods such as getting used to waste processing behavior from an early age. Waste processing behavior is included in environmental literacy. This ability involves knowledge, skills, and awareness of various environmental issues. This study was conducted to see the effect of the environmental-based Project Based Learning model on students' environmental literacy. This study used a Quasi Experiment design with a non-equivalent control group design. Students of class VIII of SMPN 24 Malang became the subjects of the study with samples of classes VIII-F and VIII-G. The analysis method used the Independent Sample T-Test to see the differences between the experimental class and the control class. Based on the test results, it was found that there was a significant difference in the post-test scores of the two classes. This proves that the project-based learning model is more effective in improving environmental literacy in students.